Studi Pengaruh Penambahan Abu Batu Sebagai Pengganti Pasir Pada Beton Mutu K-250 - Listiawaty, H.; Namira, S.A.; Aryasin, M.; Muhajir, M.; Martani, S.W. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2025)
The handling of stone ash waste from the by-product of the Quarry C crushed stone factory with the number of factories along the Palu-Donggala road has not been handled properly until now. The potential for utilization for building materials such as lightweight concrete, paving blocks and rosters as well as fillers for asphalt concrete mixtures and rigid pavements at airports is still large to be developed. Based on this, stone ash waste can be used as a building material to build structures and infrastructure. However, the characteristics of the basic materials and building materials made from stone ash waste must be re-tested. The analysis was carried out on the results of the concrete compressive strength test (SNI 03-1974-2011), which is a comparative analysis of various conditions of the age of the test object and the percentage of stone ash addition to the weight of fine aggregate obtained from the laboratory. The addition of stone ash as a partial replacement for fine aggregate can increase the compressive strength of concrete by up to 9.64% compared to the compressive strength of normal concrete. The optimum level of stone ash addition as a partial replacement for fine aggregate occurs at a variation of 20% stone ash from the weight of fine aggregate. The compressive strength of 28-day concrete that occurs in this variation is 23.590 MPa, while the compressive strength of concrete without the addition of stone ash is 21.515 MPa. The compressive strength value of concrete with 50% rock ash content has the lowest compressive strength value of 21.137 MPa, where there is a decrease in the compressive strength value of 1.75% compared to the compressive strength value of concrete without the addition of stone ash..